2021
DOI: 10.1136/bmjgh-2020-004248
|View full text |Cite
|
Sign up to set email alerts
|

Impact and effect mechanisms of mass campaigns in resource-constrained health systems: quasi-experimental evidence from polio eradication in Nigeria

Abstract: BackgroundMass campaigns are a key strategy for delivering life-saving interventions under Global Health Initiatives, especially in weak health system contexts. They are frequently designed parallel to the health system to rapidly achieve programme targets such as vaccination coverage, but we lack quantitative evidence demonstrating their impact and effect mechanisms on health system performance at sub-/national level. This longitudinal study responds to this gap through an analysis of polio eradication campai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“… Factor Frequency Note Reference Individual factors Maternal factors Maternal literacy and education 22 High maternal education consistently associated with higher vaccination rates, although one national study found that education level was not significant when adjusted for literacy [32] . [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] Maternal care (health facility birth) 12 Giving birth in a health facility was significantly associated with vaccination, particularly for birth doses. However, delivery on weekends or outside routine vaccination days, and prematurity or low birth weight, were reasons for delayed or missed birth dose vaccinations [54] .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… Factor Frequency Note Reference Individual factors Maternal factors Maternal literacy and education 22 High maternal education consistently associated with higher vaccination rates, although one national study found that education level was not significant when adjusted for literacy [32] . [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] Maternal care (health facility birth) 12 Giving birth in a health facility was significantly associated with vaccination, particularly for birth doses. However, delivery on weekends or outside routine vaccination days, and prematurity or low birth weight, were reasons for delayed or missed birth dose vaccinations [54] .…”
Section: Resultsmentioning
confidence: 99%
“… [48] , [56] Socioeconomic factors Socioeconomic status 16 Vaccination rates consistently increased as household wealth increased. [7] , [32] , [35] , [37] , [38] , [39] , [44] , [45] , [48] , [50] , [51] , [53] , [55] , [59] , [66] , [67] Paternal / caregiver factors Paternal / caregiver support for vaccination 8 Higher paternal or parental / caregiver education, employment, awareness, and support for vaccination was also associated with higher childhood vaccination coverage. [45] , [51] , [52] , [56] , [68] , [69] , [70] , [71] , [72] Paternal permission for vaccination 6 Coverage was lower where caregivers, particularly fathers, refused permission for vaccination.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These other maternal and child health programs differ from the polio program in terms of the collaborative efforts involved in the program when compared to other programs [ 3 , 38 ]. So, they face challenges in lack of extensive funding mechanism, support from the traditional, religious, and political leaders and donors, and monetary incentives for health workers' participation.…”
Section: Discussionmentioning
confidence: 99%
“…A recent paper by Haenssgen et al [ 24 ] provides evidence that well-functioning health systems can benefit from mass campaigns but challenges the established wisdom to intensify mass campaigns in weaker health systems to bypass service provision bottlenecks. They point out that mass campaigns do not inherently benefit or damage a health system, but frequent campaigns in weak health system contexts can impede service provision, and they call for an additional burden of proof and active efforts to integrate the services delivered through mass campaigns into routine health services by harmonizing implementation plans and service delivery in weak health system contexts.…”
Section: Discussionmentioning
confidence: 99%